2000
DOI: 10.1046/j.1365-2958.2000.01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic nitrate reductase (narGHJI) activity of Mycobacterium bovis BCG in vitro and its contribution to virulence in immunodeficient mice

Abstract: Mycobacterium tuberculosis and Mycobacterium bovis cause tuberculosis, which is responsible for the deaths of more people each year than any other bacterial infectious disease. Disseminated disease with Mycobacterium bovis BCG, the only currently available vaccine against tuberculosis, occurs in immunocompetent and immunodeficient individuals. Although mycobacteria are obligate aerobes, they are thought to face an anaerobic environment during infection, notably inside abscesses and granulomas. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 33 publications
5
115
1
Order By: Relevance
“…The narGHJI operon is important for the survival of Mycobacterium bovis BCG in SCID mice (Weber et al, 2000). A narG knockout mutant of M. bovis BCG shows decreased virulence in these mice in comparison to the wild-type strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The narGHJI operon is important for the survival of Mycobacterium bovis BCG in SCID mice (Weber et al, 2000). A narG knockout mutant of M. bovis BCG shows decreased virulence in these mice in comparison to the wild-type strain.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures in NRP-1 synthesize greater levels of nitrite than do actively growing (AG) aerobic cultures, but in both cases the nitrite is produced by the nitrate reductase enzyme encoded by narGHJI (Weber et al, 2000;Sohaskey & Wayne, 2003). Expression of this operon is constitutive and not induced by hypoxia, although transcription of the narK2 nitrate transporter is.…”
Section: Introductionmentioning
confidence: 99%
“…The dormant state of M. tuberculosis closely resembles the M. bovis BCG dormant state, and both are biochemically and morphologically distinct from their respective growing states [23], and it is thought that that holds for M. bovis wild type as well. Genes that are expressed during the dormant state of both M. tuberculosis and M. bovis BCG are: hspX (encoding a-crystallin) [23,24], NarGHIJ (encoding nitrate reductase) [25], gcvB (encoding glycine dehydrogenase) and [24], sigF (encoding a stresse response transcription factor) [26]. From the above it becomes clear that in vitro, M. bovis and M. tuberculosis can go into a similar dormant state.…”
Section: Latencymentioning
confidence: 99%
“…This property is distinct from that of well-studied nitratereducing bacteria such as Escherichia coli and Bacillus subtilis, which are able to metabolize nitrate as a nitrogen source to nitrite and further to ammonia (Cole, 1996;Nakano & Zuber, 1998), and of denitrifiers such as Pseudomonas aeruginosa and Paracoccus denitrificans (Zumft, 1997). Mycobacterium bovis BCG and M. tuberculosis, which are closely related to C. glutamicum, also possess anaerobic nitrate reductase encoded by a narGHJI gene cluster (Sohaskey & Wayne, 2003;Weber et al, 2000), although these bacteria are unable to grow in the absence of oxygen. The nitrate reductase activity of M. tuberculosis cells is strongly induced during chronic infection of mice and under in vitro conditions of gradual oxygen depletion, which are the conditions established to provide a model of the dormant state with latent tuberculosis (Shi et al, 2005;Sohaskey & Wayne, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that nitrate respiration plays a role in the survival of the pathogen during the inhibition of aerobic respiration (Sohaskey, 2008). Notably, a narG mutant of M. bovis BCG showed reduced virulence and lung damage in both immunocompetent and immunodeficient SCID mice (Fritz et al, 2002;Weber et al, 2000).…”
Section: Introductionmentioning
confidence: 99%